Pengaruh Kurs Dollar Amerika, Cadangan Devisa Dan Produk Domestik Bruto Terhadap Impor Makanan Dan Minuman Di Indonesia - Aditya, I Gusti Made; Wirawan, I Gusti Putu Nata (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Indonesia is a developing country where the industrial sector has not been able to meet all domestic demand, especially in commodity food and drinks. Classical theory by David Ricardo stated that a country would benefit from international trade if the product specialization and exporting goods in which the country can produce relatively more productive as well, where the country's imported goods relatively less productive or unproductive, with this consideration, Indonesia entry in international trade. This study aimed to analyze the influence of the US dollar exchange rate, foreign exchange reserves and gross domestic products imultaneously and partially to the value of imports of food and drinks in Indonesia in 1993-2012, and analysis techniques used are multiple linear regression analysis technique. The results of the data analysis F test showed that the US dollar exchange rate, foreign exchange reserves and gross domestic product an effect simultaneously to the value of imports of food and drinks in Indonesia in 1993-2012. The result of partial test (t) which indicates, the US dollar exchange rate variable negative and significant, variable Foreign Exchange Reserves positive and significant and gross domestic product has no effect on imports of food and drinks in Indonesia in 1993-2012.
Keywords: Makanan dan Minuman; Impor; Kurs; Pendapatan